An exploration of social entrepreneurship in Khayelitsha, South Africa : supporting local solutions to local problems through transdisciplinary research - Pauw, Ivan (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2021.